POTRET ETIKA ERA YUNANI - Hasbie Rois Abdillah Hasbie Rois (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Ethics is the science that explains the issue of good and bad and about moral rights and obligations. The teachings of ethics began to be coined for the first time in ancient Greece. Therefore, this study aims to explain ethics in the Greek era. This research is included in the category of library research (liberary research). The data collected in this study used the documentation method, then analyzed using the analytical descriptive method. The results of this study indicate that ethical knowledge continued to develop until the Soclassic period, which among the philosophers at that time were Socrates, Plato and Aristotle. Socrates said that ethics is an issue that relates to humans and relates to the practical life of humans. Plato mentions ethics as an idea. According to him, the highest idea is the good and the meaning of human existence is to achieve the highest idea by recognizing reason and freeing oneself from the power of lust. While Aristotle in classifying philosophy, he divided philosophy into three fields of study, namely speculative or theoretical philosophy, practical philosophy and productive philosophy. Ethics is included in practical philosophy, namely philosophy that provides instructions for good human behavior. After that, Greek philosophy declined during the Hellenic era. At that time there were three teachings on ethics, namely: the first is skepticism, according to this school it is impossible for humans to achieve certainty and knowledge if they do not believe quickly, however, if humans want to achieve peace of mind, then they must not make decisions. a man who does not make decisions, then he is never wrong. The second, epicurism, this school says if humans want to get peace then he must eliminate his own fear. Finally, stoaism, this teaching views that truth does not lie in the understanding that is in itself, but lies in the incorporation of understanding in an assessment.